2007
DOI: 10.1001/archpsyc.64.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Risk of Alzheimer Disease

Abstract: Context: Social isolation in old age has been associated with risk of developing dementia, but the risk associated with perceived isolation, or loneliness, is not well understood.Objective: To test the hypothesis that loneliness is associated with increased risk of Alzheimer disease (AD).Design: Longitudinal clinicopathologic cohort study with up to 4 years of annual in-home follow-up.Participants: A total of 823 older persons free of dementia at enrollment were recruited from senior citizen facilities in and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
895
7
18

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 1,123 publications
(948 citation statements)
references
References 53 publications
28
895
7
18
Order By: Relevance
“…Other new risk factors include diet and recent weight loss and this was also not assessed properly. 95,96 There is also recent evidence that loneliness and chronic distress increase the risk of AD, [97][98][99] but these psychological factors were not assessed in this study. Finally, we did not assess formally for the use of particular medications with anticholinergic side effects, which have been found in 9% of MCI subjects.…”
Section: Discussionmentioning
confidence: 83%
“…Other new risk factors include diet and recent weight loss and this was also not assessed properly. 95,96 There is also recent evidence that loneliness and chronic distress increase the risk of AD, [97][98][99] but these psychological factors were not assessed in this study. Finally, we did not assess formally for the use of particular medications with anticholinergic side effects, which have been found in 9% of MCI subjects.…”
Section: Discussionmentioning
confidence: 83%
“…A study analyzing the association between social isolation and AD showed that the risk of developing AD was more than doubled in isolated person. Social isolation was associated with lower level of cognition at baseline and with more rapid decline during follow-up (Wilson et al, 2007). However, social isolation was not related to any change of the brain hallmarks associated with AD suggesting that social isolation may contribute to risk of AD and does so through some mechanisms other than AD pathology.…”
Section: Introductionmentioning
confidence: 85%
“…• Diminished physical activity 13 • Diminished motor function 14,15 • Symptoms of depression 16 • Disrupted sleep and daytime dysfunction 17 • Impaired mental and cognitive function 18 • Increased systolic blood pressure 19 • Increased sympathetic tone and vascular resistance 20,21 • Increased hypothalamic pituitary adrenocortical activity 22,23 • Altered gene expression related to anti-inflammatory responses 24 • Altered immunity 25,26 Of greater concern, however, is an accumulating volume of research that highlights loneliness as a risk factor for both functional decline as well as increased mortality. 4,8,[27][28][29] In short, there is evidence that the subjective experience of loneliness can significantly contribute to premature death independently of other physical, behavioral, or psychological factors.…”
Section: Effects Of Lonelinessmentioning
confidence: 99%